2012
DOI: 10.3758/s13414-012-0377-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of marker-related temporal cues on auditory gap-duration discrimination

Abstract: In three experiments, we examined the ability of listeners to discriminate the duration of temporal gaps (silent intervals) and the influence of other temporal stimulus properties on their performance. In the first experiment, gapduration discrimination thresholds were measured either in continuous noise or with noise markers with durations of 3 and 300 ms. Thresholds measured with 300-ms markers differed from those measured in continuous noise or with 3-ms markers. In the second experiment, stimuli consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Individual and group mean data across four runs per condition are depicted in figure 2. Gap-length JNDs following the 5000 ms retention interval approximated 26 ms. Abel (1972) and Stellmack et al (2013) reported comparable results for similar duration temporal markers even though procedures differed, and the retention interval was five-to-ten times larger in the present study. There was no significant difference in JND by condition (F 2, 10 = 2.72, p = 0.38) per a repeated-measures ANOVA with Geisser-Greenhouse adjustment.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Individual and group mean data across four runs per condition are depicted in figure 2. Gap-length JNDs following the 5000 ms retention interval approximated 26 ms. Abel (1972) and Stellmack et al (2013) reported comparable results for similar duration temporal markers even though procedures differed, and the retention interval was five-to-ten times larger in the present study. There was no significant difference in JND by condition (F 2, 10 = 2.72, p = 0.38) per a repeated-measures ANOVA with Geisser-Greenhouse adjustment.…”
supporting
confidence: 72%
“…Maintaining the resolution of time-based associations amongst auditory objects would allow listeners to establish coherent-cognitive representations of pertinent, ongoing events (Engle et al 1999). Establishing such time-based relationships between acoustic events involves retention and comparison of temporal markers (Abel 1972;Plomp 1964) with onset times between fixed-duration temporal markers being a robust indicator (Stellmack et al 2013). While this suggests possible use of rhythm cues, modeling indicates that temporal gaps themselves may provide useful information.…”
mentioning
confidence: 99%
“…Many factors may have influenced the performance on the two tests, including the randomness of the gap, location of the gap, and the duration of the noise in which the gap was inserted. On the basis of the findings of Stellmack, Viemeister, Byrne, and Sheft (2013), it can be inferred that the randomness and location of the gaps probably resulted in the difference in performance between the two tests rather than the duration of the noise. Stellmack et al noted that gap-discrimination thresholds were better for a continuous noise having gaps interspersed at set intervals compared to noise markers having a duration of 300 ms with a gap in its center.…”
Section: Discussionmentioning
confidence: 95%